Pemberian Air Kelapa Muda terhadap Penurunan Tekanan Darah pada Lansia Ny. R dengan Hipertensi di Wilayah Kerja Puskesmas Putri Ayu, Kota Jambi - Prasani, Mutiara; Mekeama, Luri (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2024)
Background: In 2023, people aged 65-74 years (62.21%) will be found to suffer from hypertension. Putri Ayu Community Health Center in May 2024 there were 210 cases of elderly hypertension. Uncontrolled hypertension causes complications and even death. One innovation to lower blood pressure is giving young coconut water. Objective: To find out the nursing care of Mrs. R by providing young coconut water to reduce pressure in the working area of ​​the Putri Ayu Health Center, Jambi City. Methods: The method used in this research is a case report. Researchers provided nursing care to one elderly person, namely Mrs. R who suffers from hypertension. The innovation carried out by researchers was giving young coconut water to lower blood pressure. Blood pressure measurements are carried out using a stethoscope and a blood pressure monitor using an observation sheet. Researchers also used Standard Operating Procedure (SOP) guidelines for administering young coconut water. Nursing care will be provided on June 8-12, 2024. Results: Blood pressure on the first day before administration was 170/100 mmHg, and after administration for 3 days it was 145/85 mmHg. Conclusion: Giving young coconut water can reduce blood pressure in hypertensive patients. The community health center is expected to remain active in providing direction and education regarding the importance of maintaining stable blood pressure.